Determinations of the area needed for the family farm to reach a viable economic size - Eduard Alexandru Dumitru; Cristina Maria Sterie (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The high number of subsistence and semi-subsistence farms is due to their small economic size, mainly due to the low efficiency of the crops grown in relation to the small area they cultivate. Using the Simplex method, the areas that family farms would need to farm in order to ensure a normal living for all family members were determined. The aim of this study is to identify the economic size of family farms and to create scenarios that indicate to farmers the categories of crops they can cultivate in order to reach the determined economic size, thus ensuring a normal/optimal standard of living for family farm members.
Keywords: Q10; Q12; Q14; Q19; 330; family farm; rural development; Romania; sustainable